Exegesis in the making postcolonialism and New Testament studies - Runesson, Anna (Leiden Boston Brill, 2011)
Known for its fresh approaches as well as for its complex theoretical foundations, postcolonialstudies is one of the most dynamic contributions to the field of biblical studies today. The presentbook is a pedagogically structured introduction to this emerging field for both scholar and student
Includes bibliographical references (p. [235]-248) and index. - Description based on print version record
Online-Ausg.
Keywords: Bible -- Postcolonial criticism; Bible -- Postcolonial criticism; Bible. N.T; Bible. N.T -- Postcolonial criticism; Bible; Postcolonial criticism of sacred works; Religion; Philosophy & Religion; Christianity; RELIGION ; Biblical Criticism & Interpretation ; New Testament; Electronic books